DEFINISI DAN KONSEPSI FALSAFAH ISLAM - Nanang Tahqiq (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2015)
This academic manuscript intensely and scrupulously examines convolutions within the definition of Islamic Philosophy. Entirely numerous genres of meanings on the Islamic falsafa lavishly subsist, and the writer has uncovered thirteen outlooks. Each of them holds its own reason, intention and locale background. However, the article will only deal with six definitions. Apart from definition, the article portrays polemics and paradoxes dealing with terms of falsafa renowned in the Indonesian common parlance.